Implementasi Pengelompokan Persediaan Sepeda Motor Menggunakan Metode Clustering K-Means - Azhar, Zulfi; Wulandari, Chairani; Hanum, Zulia; Arfansyah Putra, Wan; Puspita Saragih, Yenny (Explorer, 2024)
Designing an annual marketing strategy for motorbike inventory in each city where previous data already exists but sometimes has never been reviewed. Decision making in determining the number of Honda brands that consumers are interested in per year needs to be reviewed in each city. CV. Karya Utama Kisaran, a company engaged in marketing motorbikes which is experiencing an increasingly competitive level of business competition. This requires determining motorbike inventory which can increase motorbike sales volume by choosing the right dealer. Motorbike inventory is one of the things that needs to be done in designing marketing strategies in several cities. In this analysis process, it is carried out using data mining with clustering techniques which use non-hierarchical methods in non-hierarchical grouping, one single data in a group, or more small groups that can combine into a large group. The aim of the research is to determine the similarity in characteristics between the data in inventory transaction database, in order to form groups of marketing locations. The final results of the research carried out produced 2 clusters where cluster 1 was City 1, 2, 4, 6, 7, 8,9,10, 11,12 and cluster 2, City 3 and 5 from a total of 12 cities, by showing that cluster 2 has higher motorbike inventory and marketing than cluster 1.